Prey Capture Behavior Evoked by Simple Visual Stimuli in Larval Zebrafish - Bianco, Isaac H.; Kampff, Adam R.; Engert, Florian (Frontiers in Systems Neuroscience, 2011)
Understanding how the nervous system recognises salient stimuli in the environ- ment and selects and executes the appropriate behavioural responses is a fundamen- tal question in systems neuroscience. To facilitate the neuroethological study of visually-guided behaviour in larval zebrafish, we developed “virtual reality” assays in which precisely controlled visual cues can be presented to larvae whilst their behaviour is automatically monitored using machine-vision algorithms. Freely swimming larvae responded to moving stimuli in a size-dependent manner: they directed multiple low amplitude orienting turns (∼ 20◦) towards small moving spots (1◦) but reacted to larger spots (10◦) with high-amplitude aversive turns (∼ 60◦). The tracking of small spots led us to examine how larvae respond to prey during hunting routines. By analysing movie sequences of larvae hunting parame- cia, we discovered that all prey capture routines commence with eye convergence and larvae maintain their eyes in a highly converged position for the duration of the prey-tracking and capture swim phases. We adapted our virtual reality assay to deliver artificial visual cues to partially restrained larvae and found that small moving spots evoked convergent eye movements and J-turns of the tail, which are defining features of natural hunting. We propose that eye convergence represents the engagement of a predatory mode of behaviour in larval fish and serves to increase the region of binocular visual space to enable stereoscopic targeting of prey.